Resistive Shaping of Interconnected Low-Voltage Microgrids Operating Under Distorted Voltages - Alonso, Augusto Matheus dos Santos; Brandao, Danilo Iglesias; Tedeschi, Elisabetta -; Marafao, Fernando Pinhabel (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Beyond the impacting presence of non-linear loads, low-voltage microgrids also experience low energy efficiency and resonance phenomena when operating interconnected to a distribution grid that suffers from distorted voltages. This paper proposes a model-free control strategy capable of coordinating inverters existing within a dispatchable microgrid, allowing to operate it as a single-controllable entity that behaves like a resistor at selected harmonic frequencies. Such resistive shaping uses a centralized control architecture to steer inverters to distributively compensate reactive and harmonic currents, supporting active current sharing. Consequently, the microgrid point-of-common-coupling operates with a high power factor when the grid imposes distorted voltages. Additionally, if resonant components exist, the strategy supports harmonic resonance damping, which minimizes deterioration of voltage quality. For instance, comparative results show that, for the considered scenario, the proposed resistive shaping damps resonances up to 50% better than a previous approach that compensates harmonics using sinusoidal current synthesis. Simulation results carried out on a three-phase low-voltage microgrid testbench, considering three inverters, demonstrate the above-mentioned capabilities of the proposed approach. Experimental results based on a single-phase microgrid prototype comprising two inverters with two linear loads and one non-linear load validate the applicability of the method to real-life implementations.
Keywords: Damping; Distributed generation; Harmonic analysis; Harmonic distortion; harmonics; Inverters; Microgrids; microgrids; power factor; Power harmonic filters; resonance; Voltage control